(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2022)
Due to local people’s misconceptions, a large number of wildlife species are facing threats in Bangladesh. From July 2017 to June 2021 a research work was conducted in Kashipur Union, under Barishal district of Bangladesh. In total, 191 vertebrate wildlife species were recorded. 141 species (74.35%) were bird, 18 species (9.42%) mammals, 17 species (8.90%) reptiles and 15 species (7.85 %) were amphibians. The largest diversity of animals (148 species) and their abundance (n=1477) were counted in winter. Bird species diversity was high in winter (H=4.699, Ds=0.989) with winter migrants (24 species). The summer season had the most evenness (E= 0.7652). Among them, 82 (42.93 %) species of wildlife were very common, 20 (10.47 %) common, 36 (18.32 %) uncommon and 54 (28.27 %) were few. An amphibian species Euphlyctis kalasgramensis had the highest (24.95 %) relative abundance; Hemidactylus frenatus (22.60 %) (reptile); Turdoides striata (3.23 %) (bird); and Rattus rattus (21.94 %) (mammalian) species. Among the observed wildlife species, 183 (95.81 %) were classified as least concern followed by 4 (2.09 %) near threatened, 2 (1.04%) vulnerable and only one (0.52%) endangered. J. Biodivers. Conserv. Bioresour. Manag. 2021, 7(2): 61-72